Rheological, pasting and sensory properties of biscuits supplemented with grape pomace powder - LOU,Wenjuan (2022)
Abstract The research aimed to study the effects of 0–20% substitution of wheat flour with grape pomace powder (GPP) on the rheological and pasting properties of wheat dough, and on sensory properties, digestive and antioxidant activities of the prepared biscuits. The results of rheological analysis showed that incorporation with GPP concluded in reduced water absorption (WA) and increased dough stability. Rapid visco-analyser (RVA) results suggested GPP could increase the breakdown value of the starch paste system but decrease the setback and peak viscosity. With respect to biscuit properties, it was found that 5%–15% GPP resulted in increased chewiness and hardness of biscuits. Also, it was recorded that GPP significantly improved antioxidant activity and DPPH and hydroxyl radical scavenging capabilities. Although the in vitro digestibility results showed that the addition of GPP displayed minor influence on digestion rate, the sensory analysis results showed that the biscuits supplemented with GPP to a level of 10% resulted in products with good overall acceptability. Additionally, biscuits incorporated with an addition amount of 10% GPP exhibited nailing oxidation resistance and can be considered as a food with a high fiber content, which is a good option for people to pursue modern healthy foods.